A comparative study of thermal conductivity in ZnO- and SnO2-based varistor systems - Bueno, Paulo Roberto [UNESP]; Varela, José Arana [UNESP]; Barrado, C. M.; Longo, Elson [UNESP]; Leite, E. R. (Blackwell Publishing, 2005)
We performed a comparative study of electrical and thermal properties of ZnO- and SnO2-based varistor. The electrical properties of commercial ZnO-based varistor are equivalent to that found in SnO2-based varistor system. In spite of this, the SnO2 showed a thermal conductivity higher than commercial samples of ZnO-based varistor, which allied with its simpler microstructure and lower dopant concentration is a remarkable result that point out to the use of this system to compete commercially with ZnO-based varistor devices.